LITERATURE REVIEW (LR): THE INFLUENCE OF COMPENSATION ON TEACHER PERFORMANCE - Mei Utari, Hanny; Rindaningsih, Ida (PT. Antis International Publisher, 2025)
Objective: To examine the influence of compensation on teacher performance and its impact on the quality of education in a country. Method: This study evaluates the role of compensation—including salary, benefits, allowances, and other incentives—in motivating teachers and enhancing their performance. A qualitative approach was used to assess how adequate compensation correlates with teacher morale and effectiveness. Results: Findings indicate that sufficient compensation significantly boosts teacher motivation and performance. Teachers who feel valued through appropriate remuneration demonstrate higher morale and contribute to improved educational outcomes. Conversely, inadequate compensation can diminish teacher morale, potentially degrading the quality of education delivered. Novelty: This study highlights the critical connection between compensation satisfaction and teacher performance, emphasizing its role not only as financial support but also as a form of recognition that impacts educational quality.